Sharia Economics: Alternative Solutions for a Sustainable Economy - Junaedi Junaedi; Muhammad Mahfuz; A. Fandir; A. Fandir; Qais Ainu Rahmatika; Lila Alwyah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Recurring global economic crises show the weakness of the conventional economic system in realizing fair, inclusive and sustainable growth. Sharia economics exists as an alternative solution by offering a system based on the values of justice, balance and social responsibility. This research aims to analyze the implementation of sharia economic principles and their contribution to sustainable economic development in Indonesia. The method used is descriptive qualitative through literature studies and case studies on sharia financial institutions and zakat and waqf management institutions. The research results show that sharia economics plays a significant role in empowering the community's economy, reducing social inequality, and strengthening the real sector through usury-free financial mechanisms, zakat distribution, and productive waqf management. However, the implementation of sharia economics still faces challenges in the form of low public literacy, limited regulations, and the need to increase human resource capacity. By strengthening policies and institutional support, sharia economics has great potential as a main pillar in building a sustainable and just economy.